Coastal dynamics and geomorphology of the Pozos Colorados sector, Santa Marta: an analysis of sea level rise and paleo-shoreline - Villate-Daza, Diego Andrés; Barboza-Pinzon, Eduardo Guimarães; Jigena-Antelo, Bismarck; Muñoz-Perez, Juan José; Anfuso, Giorgio; Portz, Luana Carla; Afanador-Franco, Fernando; Manzolli, Rogério Portantiolo (Frontiers in Marine Science, 2025)
IntroductionWe assess how inherited subsurface architecture and human interventions control recent shoreline change and vulnerability in Pozos Colorados (Santa Marta, Colombian Caribbean). MethodsWe integrated geomorphological mapping, multi-decadal shoreline extraction with CoastSat (1986–2024; EPR), Ground Penetrating Radar (GPR) profiles, paleoshoreline detection from high-resolution DEM, and paleo/future sea-level scenarios. ResultsNet shoreline retreat averaged –2.0 m yr⁻¹ (max erosion in 1986–1996; localized accretion after 2021), linked to sediment budget shifts and engineering structures. GPR reveals erosional surfaces/terraces guiding present morphodynamics. Paleo sea-level highstands (MIS5e +6 m; mid-Holocene +3 m) and a 2100 SLR scenario overlap low-lying inherited surfaces.DiscussionCoupling surface (CoastSat) and subsurface (GPR) evidence clarifies multi-scale controls on instability and maps exposure hotspots, supporting ecosystem-based, adaptive coastal management in this urbanizing sector.